2016
DOI: 10.3847/0004-637x/826/2/112
|View full text |Cite
|
Sign up to set email alerts
|

Alma Imaging and Gravitational Lens Models of South Pole Telescope—selected Dusty, Star-Forming Galaxies at High Redshifts

Abstract: The South Pole Telescope has discovered one hundred gravitationally lensed, high-redshift, dusty, star-forming galaxies (DSFGs). We present 0.5 resolution 870 µm Atacama Large Millimeter/submillimeter Array imaging of a sample of 47 DSFGs spanning z = 1.9 − 5.7, and construct gravitational lens models of these sources. Our visibility-based lens modeling incorporates several sources of residual interferometric calibration uncertainty, allowing us to properly account for noise in the observations. At least 70% o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
362
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 229 publications
(405 citation statements)
references
References 83 publications
40
362
1
Order By: Relevance
“…6), there is no difference in gas masses between SPT-DSFGs and the comparison sample. Furthermore, Spilker et al (2016) found that the observed angular sizes of SPT-DSFGs (at <z>∼ 4) are consistent with the angular sizes of lower redshift unlensed DSFGs (at <z>∼ 2). Allowing for the redshift evolution of the angular scale, this implies that DSFGs in the higher-redshift SPT sample are more physically compact (1 at z = 3.5 corresponds to 7.47 kpc, while 1 at z = 2.2 corresponds to 8.42 kpc).…”
Section: Gas Densitysupporting
confidence: 63%
See 4 more Smart Citations
“…6), there is no difference in gas masses between SPT-DSFGs and the comparison sample. Furthermore, Spilker et al (2016) found that the observed angular sizes of SPT-DSFGs (at <z>∼ 4) are consistent with the angular sizes of lower redshift unlensed DSFGs (at <z>∼ 2). Allowing for the redshift evolution of the angular scale, this implies that DSFGs in the higher-redshift SPT sample are more physically compact (1 at z = 3.5 corresponds to 7.47 kpc, while 1 at z = 2.2 corresponds to 8.42 kpc).…”
Section: Gas Densitysupporting
confidence: 63%
“…Members of a flux-selected lensed sample will be biased towards being systematically compact (as a compact source lying close to a lensing caustic will be magnified more than a similarly-positioned extended source). Despite this, however, based on sizes derived from lens model fits to ALMA 870µm data Spilker et al (2016) find that the observed angular 870µm size distribution of SPT-DSFGs is statistically consistent with the distribution of 870µm angular sizes displayed by members of un-lensed comparison samples. With the higher mean redshift of the SPT-DSFG sample, and the redshift evolution of the angular scale, this implies that DSFGs in the higher-redshift SPT sample are slightly more physically compact (i.e., 1 at the mean redshift of SPT-DSFGs, z = 3.5, corresponds to 7.47 kpc, while 1 at the mean redshift of unlicensed DSFG samples, z = 2.2, corresponds to 8.42 kpc).…”
Section: Dynamical Mass and Potential Lensing Biasmentioning
confidence: 88%
See 3 more Smart Citations